Corporate Governance: Earnings Management Linkages: Impact of Audit Committee Composition and Operational Characteristics - Van der Zahn, Jean-Luc Wolfgang Mitchell (Institutional Knowledge at Singapore Management University, 2004)
Our study documents a comprehensive simultaneous analysis of the association between five-audit committee composition and operational characteristics features and earnings management based on a sample of 485 organisational-years of Singapore publicly traded organisations. Findings provide only partition support for the view organisations with a higher proportion of independent audit committee members are more effective at constraining earnings management. Organisations with audit committees that are more diligent and/or lack the presence of independent directors serving simultaneously on a substantial number of boards and committees are more effective at constraining earnings management. Audit committee expertise and the presence of a senior executive director on the committee do not appear to influence the committee's ability to constrain earnings management. Our findings are robust to alternative income-incentives facing corporate management and entices associated with different levels of ownership concentration. Overall, our findings are rich with policy and practical implications.